Relatos de la diáspora desde la obra de Quince Duncan - Mauro, María del Carmen (2012)
In Latin American cultures afrodescendants presence is notorious in all the fields of intellectual production, it’s contribution has been fundamental to rebuild the cosmogony and oral tradition, and to preserve and reconstruct identity in diaspora. The different cultural forms have transcended beyond the space of negritude and have pervaded to national thought in the Americas. In literature, resistance, fight for liberation and equality have consolidated in the hands of writers like Quince Duncan. Duncan has done it through the custody, rescue and publication of the fictional memories of people descending from Africans.